Adoption of Digital Population Identity Innovation in Pekanbaru City - Handrian, Eko; Suriani, Lilis; Hasanah, Andini Noor (UIR Press, 2026)
Innovation adoption is the process through which individuals or groups accept and use new ideas, technologies, or policies within a social system. This research focuses on the adoption of the Digital Population Identity as an effort to enhance population administration services through digitalization, with the aim of analyzing the adoption process and its inhibiting factors in Pekanbaru City. The study focuses on community behavior in accepting and using Digital Population Identity (IKD) based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) framework. This research employs a quantitative method with a survey approach targeting residents of Pekanbaru City as Digital Population Identity (IKD) users, and the data were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study show that the adoption of Digital Population Identity in Pekanbaru City remains suboptimal, where performance expectancy and price value significantly affect behavioral intention, while effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit don’t show significant effects. The barriers to Digital Population Identity adoption include the low utilization of its functions in population administration services, the underdevelopment of IKD usage as a habit and social norm, and limited public trust in digital-based population administration services. To strengthen the adoption of this innovation, continuous socialization, optimization of IKD functions and strengthening public trust in the security and benefits of Digital Population Identity usage are required.